So Then Why Did You Do It? - Dunkelberg, John; Jessup, Debra Ragin (2001)
What causes unethical behavior and what can we learn from those individuals who have had spectacular ethical lapses? The profiles of six prominent individuals, including Dennis Levine, Charles Keating, and Robert Citron are examined to try to provide some insight into what lead them down the slippery slope to criminal and unethical behavior. What we found is that all six certainly knew that they were breaking the law and most went to extra-ordinary lengths to cover up what they were doing. Additionally, we found that each individual had attained a position of authority that enabled them to break the law without being seriously challenged by others who knew, or suspected, what was being done. Each person was highly compensated for their efforts, yet, they choose to engage in unethical and illegal activities in the pursuit of just a little more money or power.
Keywords: Ethical Lapse; Slippery Slope; Illegal Activity; Unethical Behavior; Economic Growth